The Effect of the Application of Edible Coatings on or before Ultraviolet Treatment on Postharvested Longan Fruits - Mee Gie Lin; Ola Lasekan; Nazamid Saari; Siti Khairunniza-Bejo (Journal of Food Quality)
This study compared the effect of application of edible coating on or before ultraviolet treatment on postharvest longan fruits. The treated longan fruits were examined for weight loss, respiration rate, surface color changes, enzymatic activities (PPO, POD, and PAL), and total phenolic contents throughout the 7 storage days at ambient temperature. In addition, coat homogeneity was examined and cell structure of longan flesh at the end of storage was observed. The results showed that when UV was applied before coating (i.e., chitosan or carrageenan), it had relatively lower PPO and PAL activities and retained higher TPC in longan pericarp. However, the changes in enzymatic activities did not affect the surface lightness and browning index as they were more influenced by the type of coating, in which combination treatments with carrageenan showed higher surface lightness and lower browning index compared to treatment combinations containing chitosan. However, when UV treatment preceded coating, the combinations of UV plus chitosan coating produced lower PPO and PAL activities and retained better cell structure with less damage than the combinations of UV plus carrageenan coating. UV plus carrageenan coating showed relatively higher weight loss and respiration rate, with cell structure exhibiting bigger intercellular spaces at the end of storage. Therefore, application of UV treatment followed by chitosan coating was found to be the best treatment combination for controlling enzymatic activities and reducing senescence rate of longan fruits.